Role of Diffusion Weighted MRI in Maple Syrup Urine Disease: Rare Cause of Neonatal Metabolic Encephalopathy - Shah, Diva; Nirula, Apoorv; Shah, Dwiti (Journal of Nepal Paediatric Society, 2013)
The newborn presenting with neurological symptoms such as seizures or lethargy due to inborn error of metabolism is an important problem. Maple syrup urine disease (MSUD) is an inherited genetic disease, caused by a deficiency of the catalytic components of α-ketoaciddehydrogenase complex, which is responsible for the catabolism of branched-chain amino acids. The purpose of this case report is to show diffusion-weighted imaging (DWI) MRI findings of acute phase of classic form of MSUD in a newborn although this imaging findings are rare but very typical, known as “MSUD oedema”. DOI: http://dx.doi.org/10.3126/jnps.v33i3.8365 J. Nepal Paediatr. Soc. 2013;33(3):230-233